2013
DOI: 10.1016/j.bbi.2013.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid inflammatory markers in Parkinson’s disease – Associations with depression, fatigue, and cognitive impairment

Abstract: Neuroinflammation may be involved in the pathophysiology of Parkinson's disease (PD) and specifically in non-motor symptoms such as depression, fatigue and cognitive impairment. The aim of this study was to measure inflammatory markers in cerebrospinal fluid (CSF) samples from PD patients and a reference group, and to investigate correlations between non-motor symptoms and inflammation. We quantified C-reactive protein (CRP), interleukin-6, tumor necrosis factor-alpha, eotaxin, interferon gamma-induced protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
160
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(175 citation statements)
references
References 49 publications
11
160
1
3
Order By: Relevance
“…22,23,30,34 A recent clinical study examining cerebrospinal fluid revealed that C-reactive protein and monocyte chemotactic protein-1 were elevated in patients with PD and correlated with more severe symptoms of depression, a nonmotor complication of PD. 35 Of note, there were no meaningful changes in IL-6, TNF-α, or interferon gamma-induced protein-10. Clinically, positron emission tomography brain imaging with a benzodiazepine ligand reveals microglial activation in the basal ganglia and frontal and temporal cortices in patients with PD.…”
Section: Discussionmentioning
confidence: 96%
“…22,23,30,34 A recent clinical study examining cerebrospinal fluid revealed that C-reactive protein and monocyte chemotactic protein-1 were elevated in patients with PD and correlated with more severe symptoms of depression, a nonmotor complication of PD. 35 Of note, there were no meaningful changes in IL-6, TNF-α, or interferon gamma-induced protein-10. Clinically, positron emission tomography brain imaging with a benzodiazepine ligand reveals microglial activation in the basal ganglia and frontal and temporal cortices in patients with PD.…”
Section: Discussionmentioning
confidence: 96%
“…56 Measures of CSF markers, including C-reactive protein, interleukin 6, TNF-α, interferon 10, monocyte chemotactic protein 1, and macrophage inflammatory protein 1-β, in individuals with PD found inflammatory markers to be significantly associated with more severe depression, anxiety, fatigue, and cognition. 57 These independent lines of evidence therefore support inflammation as an important pathway in PD, in which perturbations might serve as biomarkers with different purposes.…”
Section: Markers Of Disrupted Inflammatory Pathwaysmentioning
confidence: 99%
“…Early in the development of dopamine transporter scan use in PD, a report linking low binding to anxiety was published [84]. Cerebrospinal fluid cytokine levels have more recently been shown to correlate with anxiety as well as depression and fatigue [85]. These results must be considered tentative.…”
Section: Anxietymentioning
confidence: 96%